The Hankel transform of causal distributions - Aguirre, Manuel A. (Universidad de Costa Rica, Centro de Investigación en Matemática Pura y Aplicada (CIMPA), 1997)
In this note we evaluate the unidimensional distributional Hankel transform of  and  and then we extend the formulae to certain kinds of n-dimensional distributions called “causal” and “anti-causal” distributions. We evaluate the distributional Hankel transform of  ,  and .